Murdoch mysteries. Season 13 [videorecording (DVD)] - Crossland, Harvey; Lee, Shereen; Bisson, Yannick, 1969-; Bisson, Yannick, 1969-; Craig, Tom, 1962-; Joy, Hélène; Jennings, Maureen (Acorn, 2020)
In Victorian Toronto, Detective Murdoch uses the latest scientific techniques to solve the city's most baffling murders.